Analisis Fungsi Penghimpunan, Pendistribusian, dan Pemberdayaan dalam Melayani Mustahik pada Masa Pandemi Covid-19 di BAZNAS Provinsi Bali - Bahrullah, Bahrullah; Kurniawati, Kurniawati; Iswahyuni, Iswahyuni (Maisyatuna, 2020)
The downturn in the economy due to the Covid-19 pandemic has made it difficult for people to meet their daily needs. Therefore, as a non-structural institution, BAZNAS Bali Province is always required to provide optimal services to mustahik in particular. This research focuses on examining: (1) How to collect BAZNAS in serving Muzakki during the Covid-19 pandemic at BAZNAS, Bali Province. (2) How was the distribution of BAZNAS in serving Mustahik during the Covid-19 pandemic at BAZNAS, Bali Province. (3) How to Empower BAZNAS in Serving Mustahics during the Covid-19 Pandemic at BAZNAS, Bali Province. The objectives of this study are (1) to determine the collection of BANAS in serving Muzakki during the Covid-19 pandemic at BAZNAS, Bali Province. (2) To find out the distribution of BAZNAS in serving Mustahik during the Covid-19 pandemic at BAZNAS, Bali Province. (3) Knowing the Empowerment of BAZNAS in Serving Mustahics during the Covid-19 Pandemic at BAZNAS, Bali Province. This type of research is descriptive qualitative. Informants were selected using purposive sampling technique. Techniques to obtain valid and accurate data, namely; interviews, observation, and documentation. Data validity includes; power of observation and triangulation. Data analysis techniques include; data reduction, data presentation and decision making.The results showed that (1) the collection of BAZNAS in serving Mustahik during the Covid-19 pandemic includes; (a) education (by involving donors during distribution), (b) promotion (through print media, social media, and electronic media), accountability (through audits by public accountants, and syar'i audits), (2) distribution carried out by BAZNAS Bali Province, namely (a) traditional consumptive distribution, (b) creative consumptive distribution, (c) traditional productive distribution, and (d) creative productive distribution. (3) Empowerment carried out by BAZNAS Bali Province, namely (a) developing, (empowering mustahik), (b) self-empowering, (protecting, defending, and looking after the weak through Universal Service).